Analisis Efektivitas Penerimaan Pajak Kendaraan Bermotor Dalam Meningkatkan Pendapatan Asli Daerah Provinsi Dki Jakarta Tahun 2020 – 2022 - Ambarwati, Ambarwati; Nurbaeti, Atissa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
During the period of 2020–2022, there was a significant fluctuation in the revenue from vehicle tax in DKI Jakarta, especially related to the decrease in the effectiveness ratio of PKB revenue, which was inversely proportional to the increase in the number of motor vehicles in DKI Jakarta. The purpose of this study is to analyze and evaluate the effectiveness of PKB in increasing the Regional Original Revenue of DKI Jakarta Province in 2020–2022, identify inhibiting factors, and analyze and evaluate efforts made to overcome obstacles in achieving PKB in increasing the PAD of DKI Jakarta Province in 2020–2022. The data analysis technique used is qualitative descriptive analysis through interviews. The method of collecting field research data is through interviews and literature studies. Interviews were conducted in a structured manner with six informants. The effectiveness of PKB revenue in DKI Jakarta Province in increasing the regional original revenue in 2020-2022 has not been effective based on three main approaches, according to Duncan's theory, especially in the goal achievement and integration approaches that have not been effective. On the other hand, the adaptation approach to PKB has been effective in adjusting policies to the dynamics of the economic and social environment. Inhibiting factors in PKB revenue contributing to increasing the Regional Original Revenue of DKI Jakarta Province in 2020-2022 include physical activity restrictions due to the COVID-19 pandemic resulting in decreased community purchasing power and difficulty in identifying motor vehicle objects outside the DKI Jakarta area, progressive tax imposition rules causing dissatisfaction among taxpayers with more than one vehicle, lack of tax compliance socialization, technical constraints in applications, data mismatch, low tax awareness, and tax avoidance practices.